Mass Psychogenic Illness among Learners at Jaforabad High School, in Hathazari, Chittagong, Bangladesh - Amin, MR; Mahmood, S; Rabbi, SF; Hossain, AA; Sharif, HM (Journal of Dhaka Medical College, 2010)
Objectives: Mass psychogenic illness involves people with real symptoms that are often triggered by misunderstood or false information. We investigated symptoms of sharing among 15 learners at a high school in Hathazari , Chittagong districts of Bangladesh. Methods: In 4th August, 2007, a student of 8th grade of jaforabad high school noticed feverish feeling in his classroom, and soon thereafter he had a headache, nausea, vertigo, tingling sensation of limbs and burning sensation of the body. Within an hour another 14 learner of different grade suffers same symptoms except fever. An investigation was performed by several government agencies. Results: We were unable to find a medical or environmental explanation for the reported illnesses. The persons who reported symptoms came from 10 classrooms scattered throughout the school. The most frequent symptoms were headache, vertigo, nausea, and abdominal pain. Blood and urine specimens of admitted 3 learners showed no evidence of organic illness. A questionnaire administered two days later show that the reported symptoms were significantly associated with female sex, seeing another ill person and knowing that a classmate was ill. Conclusions: This illness, had features of mass psychogenic illness - notably, widespread subjective symptoms thought to be associated with psychosocial impact. Key words: Mass psychogenic illness; learners. DOI: 10.3329/jdmc.v18i2.6267 J Dhaka Med Coll. 2009; 18(2) : 105-111